PERENCANAAN STRATEGIS SISTEM DAN TEKNOLOGI INFORMASI PADA BIDANG PEMASARAN DINAS KEBUDAYAAN DAN PARIWISATA JAWA TIMUR - Pattah, Mochammad Rizki Dg.; Sulistiowati, Sulistiowati; Sutomo, Erwin (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Information system development conducted at this time by the Marketing Division of Culture and Tourism of East Java is still based on the current needs and the absence of information systems planning for the future to support the business needs of the Marketing Division. The problems that appear a result it is the development of information systems becomes unfocused, not integrated of data management and impact on the big budget expenditures and continuing.To be able overcome the constraint, it is required System and Information Technology Planning can be give opinions on the needs for information systems in the future by the Marketing Division to support in achieving the vision and mission of the business. It is necessary so investing for Systems and Information Technology accordance with requirements and provide benefits can be measured by achievement of goals and objectives of the organization. Result of the research produces a document of strategic planning systems and information technology. Document of strategic planning systems and information technology that has been created contains three (3) business application projects, three (3) projects IT infrastructure, and 1 (one) 1 project manejemen SI / IT.Â Keywords : Strategic Planning Systems and Information Technology, application portfolio.